The Age and High-energy Environment of the Very Young Transiting Exoplanet TOI 1227b - Attila Varga; Joel H. Kastner; Alexander S. Binks; Hans Moritz Günther; Simon J. Murphy (The Astrophysical Journal)
The mid-M star TOI 1227 hosts among the youngest known transiting exoplanets. We have conducted new X-ray imaging and optical spectroscopic observations of TOI 1227 aimed at ascertaining its age and the influence of its high-energy radiation on the exoplanet, TOI 1227b. We obtained a definitive X-ray detection of TOI 1227 with the Chandra/High Resolution Camera-I (HRC-I), and measured its Li and H α lines using the Australian National University’s Siding Spring Observatory 2.3 m telescope (WiFeS) spectroscopy. Through spatiokinematic, isochronal, and spectral energy distribution-based modeling, we have constrained the age of TOI 1227 as lying between 5 and 12 Myr, with a best estimate of ∼8 Myr. In the context of this age, we model the evolution of the transiting exoplanet TOI 1227b, using the X-ray luminosity derived from Chandra HRC-I imaging. Our modeling suggests that TOI 1227b is currently undergoing rapid atmospheric mass loss at rates on the order of ∼10 ^12 g s ^−1 . The modeling demonstrates that the exoplanet’s predicted future evolution depends sensitively on assumptions for total and core planet mass, highlighting the importance of follow-up observations of the TOI 1227 star–exoplanet system to enable measurements of both planetary mass and mass-loss rate.